100 Years of African Missions Essays in Honor of Wendell Broom - Granberg, Stanley E. (Abilene Christian University Press, 2001)
The wide-ranging essay collection is organized into four main sections. Section I introduces Wendell Broom. Secton II is "God's Call to a Continent: People and Places." Section III is "Mission Strategies and Issues." Section IV, is entitled "Concluding Thoughts" and shares some concluding thoughts on the future of African missions and the African church. The final chapter offers a speech by Wendell Broom from 1997 to 178 Nigerian evangelists and church leaders which challenged them (and us) to fill in the unevangelized gaps of Africa with a deliberate church-planting strategy to join the churches of West and East Africa by "meeting in the middle." The book concludes with an extensive bibliography of books, research, and articles on African missions by missionaries and authors associated with the Churches of Christ.